ANALISIS EFEKTIVITAS STRATEGI ADAPTASI MANAJEMEN PT. ASTRA MOTOR SUMBAWA BESAR DALAM MENINGKATKAN PENJUALAN DI ERA REVOLUSI INDUSTRI 4.0 - Syafitri, Nurul Aini; Usman, U (Fakultas Ekonomi dan Manajemen, 2025)
This study aims to know the Human Resource Management Adaptation Strategy in the Industrial Revolution 4.0 Era at PT Astra Motor Sumbawa and the effectiveness of the strategy. The type of this study was qualitative descriptive study. The types of data used were qualitative and quantitative data, then source of data in this study were primary and secondary data. The numbers of informants in this study were 4 informants consisted of 1 key informant and 3 main informants. The tools used to collect data were interviews and documentation. The technique of analysis data were qualitative analysis and effectiveness analysis. The results of this study showed that the management of PT. Astra Motor Sumbawa Besar has implemented several adaptive strategies to maintain the company's existence and increase its sales volume in the era of the industrial revolution 4.0. However, the implementation of this strategy has not shown effective results as measured by sales volume. The sales ratio at PT. Astra Motor Sumbawa Besar in 2020-2024 was in the fairly effective category, indicating that the company's management has not been able to implement an adaptive marketing strategy in accordance with changing market conditions and consumer behavior. Therefore, optimal efforts are needed from company management to explore all the potential that is owned so that it is hoped that it can provide a positive and significant contribution to increasing the company's sales volume.